An Analysis of Syllable Division Rules in English Spelling Patterns - Afrizah, Andien; Purnama, Dirza Rizki; Kinanti, Kinanti; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study investigates how syllable division rules influence English spelling patterns and their pedagogical implications in language learning. Despite the irregular nature of English orthography, this research finds that consistent patterns particularly VC/CV structures and morphemic boundaries can guide learners in decoding and spelling. Through qualitative analysis of vocabulary samples, student writings, and classroom observations, the study reveals that many spelling errors stem from a lack of syllable awareness. Furthermore, it demonstrates that integrating syllable-based instruction improves decoding strategies, orthographic memory, and reading fluency. Challenges such as individual learner differences and English's etymological complexity are also addressed. Ultimately, the study advocates for explicit syllable instruction to enhance literacy outcomes.